2003
DOI: 10.1144/0016-764902-110
|View full text |Cite
|
Sign up to set email alerts
|

Structural styles in the Zagros Simple Folded Zone, Iran

Abstract: Arabia–Eurasia convergence is achieved in the NW Zagros by a combination of shortening on NW–SE-trending folds and thrusts, mainly in the Simple Folded Zone, and by right-lateral strike-slip on the NW–SE-trending Main Recent Fault. A balanced and restored cross-section across this part of the range indicates c . 49 km of shortening. This probably occurred since c . 5 Ma, providing an estimate of the long-term shortening rate across the Simple Folded Zone of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
266
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(286 citation statements)
references
References 42 publications
18
266
1
1
Order By: Relevance
“…Blanc et al 2003;McQuarrie, 2004;Carruba et al 2006;Sepehr, Cosgrove & Moieni, 2006;Sherkati, Letouzey & Frizon de Lamotte, 2006;Mouthereau et al 2007) (Fig. 3).…”
Section: A Deformation Style Of the Cover Rocksunclassified
See 3 more Smart Citations
“…Blanc et al 2003;McQuarrie, 2004;Carruba et al 2006;Sepehr, Cosgrove & Moieni, 2006;Sherkati, Letouzey & Frizon de Lamotte, 2006;Mouthereau et al 2007) (Fig. 3).…”
Section: A Deformation Style Of the Cover Rocksunclassified
“…Some authors propose imbrication of the basement below the detached cover (Sherkati, Letouzey & Frizon de Lamotte, 2006;Mouthereau, Lacombe & Meyer, 2006;Mouthereau et al 2007;Carruba et al 2006), while others suggest that large thrust faults with significant displacement cut through basement and cover (Blanc et al 2003;Alavi, 2007). McQuarrie (2004) presented a discussion on the involvement of the basement in the deformation and concluded that most probably the cover is detached from the basement in the Lurestan and the Fars, with the basement only involved in the internal parts of the fold-thrust belt.…”
Section: A Deformation Style Of the Cover Rocksmentioning
confidence: 99%
See 2 more Smart Citations
“…The Zagros Mountains and the foreland are currently seismically extremely active. Recent GPS measurements indicate that the Arabian plate continues to move northwards relative to the Iranian microplate at rates of 20 ± 5 mm yr −1 (Tatar et al 2002;Blanc et al 2003;Nilforoushan et al 2003;Allen, Jackson & Walker, 2004;Allen et al 2006;Vernant et al 2004;Rielinger et al 2006;Walpersdorf et al 2006).…”
Section: Geological Settingmentioning
confidence: 99%